Selective Catalytic Isomerization of β‐Pinene Oxide to Perillyl Alcohol Enhanced by Protic Tetraimidazolium Nitrate. Issue 4 (28th April 2021) - Li, Hui; Liu, Jian; Zhao, Juan; He, Huiting; Jiang, Dabo; Kirk, Steven Robert; Xu, Qiong; Liu, Xianxiang; Yin, Dulin
Abstract: A series of tetraimidazolium salts with different anions was prepared and applied in the isomerization of β‐pinene oxide. After examining the activity of different catalysts, a remarkable enhancement of the selectivity of perillyl alcohol (47 %) was obtained over [PEimi][HNO3 ]4 under mild reaction conditions and using DMSO as the solvent. Furthermore, noncovalent interactions between solvent molecules and the catalyst were found by FT‐IR spectroscopy and confirmed by computational chemistry. The homogeneous catalyst showed excellent stability and was reused up to six times without significant loss. Abstract : A green option : A protic tetraimidazolium salt has been employed as a pseudo homogeneous catalyst for the isomerization of β‐pinene oxide to highly selective perillyl alcohol under mild reaction conditions. The investigated system creates a noncovalent interaction with the solvent that results into a synergistic catalysis process, thus providing evidence for an imidazole‐buffered acid‐base mechanism that allows the conversion of biomass into high value‐added chemicals.